1995
DOI: 10.1111/j.1748-1716.1995.tb09927.x
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic hamstring/quadriceps strength ratio: influence from joint angular velocity, gravity correction and contraction mode

Abstract: This study investigated isokinetic peak- and angle-specific hamstring/quadriceps strength ratios (conventional H/Q ratio) obtained during concentric and eccentric muscle contraction and examined the influence of joint angular velocity and the effect of gravity correction on these ratios. Also, a 'functional' H/Q ratio was defined by calculating eccentric hamstring strength relative to concentric quadriceps strength (Hecc/Qcon' representative for knee extension) and calculating concentric hamstring strength rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
216
3
14

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 247 publications
(239 citation statements)
references
References 15 publications
6
216
3
14
Order By: Relevance
“…Previous investigations determined the eccentric peak torque for hamstrings to concentric quadriceps during fast knee extension. Aagaard et al [14,21] reported that functional H/Q increased above 100% with rising velocity and more extended knee joint positions. similarly, Gerodimos et al [27] demonstrated that this functional ratio increased with the growth of angular velocity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous investigations determined the eccentric peak torque for hamstrings to concentric quadriceps during fast knee extension. Aagaard et al [14,21] reported that functional H/Q increased above 100% with rising velocity and more extended knee joint positions. similarly, Gerodimos et al [27] demonstrated that this functional ratio increased with the growth of angular velocity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, schiltz et al [28] revealed the results of functional H/Q at 30 deg · s -1 /240 deg · s -1 velocities to be approximately 131% (dominant limb) and approximately 126% (non-dominant limb) in professional players. Thus, the functional H/Q > 100% during fast knee extension indicated the ability of eccentrically acting hamstrings to produce a braking joint flexor moment greater than the joint extensor moment exerted by the quadriceps [14,16,21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations